Phenotypic variability of R117H-CFTR expression within monozygotic twins. (August 2016) - Waller, Michael D.; Simmonds, Nicholas J.
Summary: Whilst cystic fibrosis is a monogenic condition, variation in phenotype exists for the same CFTR genotype, which is influenced by multiple genetic and non-genetic (environmental) factors. The R117H-CFTR mutation has variability directly relating to in cis poly-thymidine alleles, producing a differing spectrum of disease. This paper provides evidence of extreme phenotype variability – including fertility status – in the context of male monogenetic twins, discussing mechanisms and highlighting the diagnostic and treatment challenges.